ASURANSI SYARIAH DI INDONESIA (Studi Tentang Peluang ke Depan Industri Asuransi Syariah) - Effendi, Afif (Kopertais Wilayah X Jawa Tengah, 2016)
AbstractThe term of takaful originates from Arabic verb â€kafalahâ€ which means â€to help one anotherâ€ or â€mutual guaranteeâ€. Now takaful can be defined as an IslamicÂ insuranceÂ concept which is grounded in IslamicÂ muamalat, and regulations ofÂ Islamic law. This concept has been practiced in various forms. Theoretically, Takaful is perceived as cooperative or mutual insurance, where members contribute a certain sum of money to a common pool.Â Takaful is invited since commercial/conventional insurance is prohibited in Islamic law. Commercial/conventional insurance is strictly disallowed for Moslem because it contains the elements of gharar (uncertainty), maysir (gambling), and riba (usury).Islamic Insurance or Sharia Insurance is based on mutual cooperation, responsibility, assurance, protection and assistance between groups of participants.Â Sharia Insurance gives members the opportunity to benefit in two ways ; from the financial security of a risk sharing arrangement, and from the spiritual benefit. IndonesiaÂ IslamicÂ Insurance Association (AASI)Â said the growthÂ of TakafulÂ industryÂ in 2013Â reachedÂ 30-40 per cent.Â This yearÂ isÂ expected better than before because Indonesia has prospect for the insurance industry to grow.Keywords: Islamic Law, Risk Sharing, Mutual Cooperation